Microbial Community, Newly Sequestered Soil Organic Carbon, and δ15N Variations Driven by Tree Roots - Song, Wenchen; Tong, Xiaojuan; Liu, Yanhong; Li, Weike (Frontiers in Microbiology, 2020)
Rhizosphere microbes in forests are key elements of the carbon sequestration of terrestrial ecosystems. To date, little is known about how the diversity and species interactions of the active rhizomicrobial community change during soil carbon sequestration and what interactions drive these changes. In this study, we used a combination of DNA and stable isotope method to explore correlations between the composition of microbial communities, N transformation and the sequestration de novo of carbon in soils around Pinus tabuliformis and Quercus variabilis roots in North China. Rhizosphere soils from degraded lands, primary stage land (tree roots had colonized in degraded soil for 1 year) and nature forest were sampled for analyses. The results showed that microbial communities and newly sequestered soil organic carbon contents changed with different tree species, environments, and successive stages. The fungal unweighted and weighted UniFrac distances could better show the different microbial species structures and differences in successive stages. Newly sequestered soil organic carbon was positively correlated with the bacterial order Rhizobiales (in Pinus tabuliformis forests), the fungal order Russulales (in Quercus variabilis forests), and δ15N. Consequently, the bacterial order Rhizobiales acted as an important taxa for Pinus tabuliformis root-driven carbon sequestration, and the fungal order Russulales acted as an important taxa for Quercus variabilis root-driven carbon sequestration. The two plant species allocated root exudates to different portion of their root systems, which in turn altered microbial community composition and function. The δ15N of soil organic matter could be an important indicator to estimate root-driven carbon sequestration.